Diskriminasi Gaya Hidup Hijabers dalam Berita Wolipop: The Reality of Hijabers Life in Online Media - RR. Pramesthi Ratnaningtyas (Jurnal Riset Komunikasi (JURKOM), 2021)
The study aims to look at the description of women wearing hijab from various countries who have been received discrimination reported in the Wolipop Hijab Articles throughout 2019. 18 articles are found related to incidents of discrimination, rejection, and prohibitions faced by Muslim women in the world. The articles is analyzed using a qualitative approach with Michel Foucault's discourse analysis method. The two main focuses of Foucault's discourse are discourse production and marginalized discourse. The results show that Wolipop constructs a reality that hijabers are still in the realm of struggle to maintain their choice of dress, as well as get their rights or achieve the position and ideals they want, eventhough they are become target of violence. Wearing hijab is a struggle for rights for Muslim women in many countries. It is not only related to religion but also the way of life and everything that is believed spiritually, although the power to perpetuate stereotypes against hijabers is not in question.